2018
DOI: 10.1159/000488587
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Hypointense Vessel Sign on Susceptibility-Weighted Imaging Is Associated with Clinical Outcome in Acute Ischaemic Stroke

Abstract: Background: Prominent hypointense vessel sign (PHVS) is visualized on susceptibility weighted-imaging (SWI) in acute ischaemic stroke (AIS). We aim to test if PHVS is associated with stroke outcome. Methods: Forty patients with acute middle cerebral artery occlusion were recruited. The presence of PHVS, cortical vessel sign (CVS), brush sign (BS) and susceptibility-diffuse weighted imaging mismatch (S-D mismatch) and Alberta Stroke Program Early CT Score (ASPECTS) on SWI were compared between the good outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 24 publications
1
31
1
Order By: Relevance
“…During the initial search, 1,018 studies were identified, 954 were initially screened by title and abstract, and 65 were assessed via a full-text review for eligibility. A total of 15 studies presented a relationship between T2*MRI findings and clinical/radiological outcomes in ischemic stroke patients after reperfusion therapy [ 5 , 13 - 26 ]. One study was a randomized controlled trial, while the other enrolled studies were observational studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the initial search, 1,018 studies were identified, 954 were initially screened by title and abstract, and 65 were assessed via a full-text review for eligibility. A total of 15 studies presented a relationship between T2*MRI findings and clinical/radiological outcomes in ischemic stroke patients after reperfusion therapy [ 5 , 13 - 26 ]. One study was a randomized controlled trial, while the other enrolled studies were observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…Although we enrolled six studies by consensus after reviewing the figures and contexts of each, the definition of prominent hypointense vessel signs ( Fig. 1B ) at the ipsilateral side of stroke and its assessing methods were not consistent in six studies [ 21 - 26 ]. Thus, we did not conduct the pooled analysis for studies of PHVS.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggest that ACVS could be used as an indicator of hypoperfusion in patients with ICA stenosis (Mundiyanapurath et al., 2016) and acute thromboembolic occlusion (Baik et al., 2012). The mismatch between ACVS on SWI and lesions on DWI corresponds to the penumbra of the acute infarct (Lou et al., 2014; Wang et al., 2018). However, the utility of ACVS in predicting the prognosis of AIS patients with IVT remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility‐weighted imaging (SWI), an MRI sequence that is highly sensitive to paramagnetic materials such as deoxyhemoglobin and hemosiderin (Huang et al., 2012; Miyasaka et al., 2012), can provide indirect information on regional perfusion status (Kao, Tsai, & Hasso, 2012). In recent years, the novel SWI‐MRI marker asymmetrical cortical vessel sign (ACVS) has been associated with poor outcomes in anterior circulation AIS patients who had not undergone IVT therapy (Sun et al., 2014; Wang et al., 2018). However, to our knowledge, there has been no study of ACVS in patients following IVT.…”
Section: Introductionmentioning
confidence: 99%
“…The PVS predicted infarct growth, early neurological deterioration, and poor outcome. 1,2 However, there is a lack of data showing how the PVS present on SWI may change dynamically.…”
Section: Discussionmentioning
confidence: 99%